Radiotherapy for prevention or management of gynecomastia recurrence: Future role for general gynecomastia patients in plastic surgery given current role in management of high-risk prostate cancer patients on anti-androgenic therapy. Issue 11 (November 2021) - Safran, Tyler; Abi-Rafeh, Jad; Alabdulkarim, Abdulaziz; Roberge, David; Luc, Mario
Summary: Purpose: Several technologies and innovative approaches continue to emerge for the optimal management of gynecomastia by plastic surgeons; the present study investigates the role of radiation therapy in this context. Methods: A systematic review was performed to evaluate the utility of radiotherapy for the prevention and treatment of gynecomastia incidence or recurrence by plastic surgeons. Results: Fifteen articles met the inclusion criteria for review. The mean incidence of gynecomastia was 70% in the high-risk population examined representing prostate cancer patients on estrogen or anti-androgen therapy. Radiotherapy was shown to significantly reduce the incidence to a median of 23%, with all six randomized control studies assessed demonstrating a statistically significant decrease in incidence following radiotherapy prophylaxis. Doses examined ranged from 8 to 16 Gy, delivered between 1 and 11 fractions. Complications following radiotherapy were minor and self-limiting in all cases, restricted to minor skin reactions, and associated with larger radiotherapy doses delivered in fewer fractions. The median complication rate was 12.4% with no major complications, such as neoplastic, pulmonary, or adverse cardiac outcomes. While the efficacy of radiation therapy as a treatment modality for gynecomastia was also established, it was shown to be less effective than other available options. Conclusions: Low-dose radiotherapy to the male breast might be a safe and effective strategy to prevent gynecomastia incidence or recurrence in high-risk patients; further studies are indicated within the common gynecomastia population managed by plastic surgeons to assess the clinical and economical utility of this intervention before a recommendation for its ubiquitous adoption in plastic surgery can be made to continue improving outcomes for high-risk gynecomastia patients.